2019
DOI: 10.1063/1674-0068/cjcp1812285
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the ligated Ag60 nanoparticle [{Cl@Ag12}@Ag48(dppm)12] (where dppm=bis(diphenylphosphino)methane)

Abstract: A novel bisphosphine ligated Ag60 nanocluster, [{Cl@Ag12}@Ag48(dppm)12], has been discovered and characterized by X-ray crystallography. It consists of a central chloride located inside an icosahedral silver core layer, which is further encased by a second shell of 48 silver atoms/ions, which are capped with 12 bis(diphenylphosphino)methane (dppm) ligands. Due to lack of sufficient material the cluster could not be further characterized by other methods. DFT calculations were carried out on the cation [{Cl@Ag1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…It should be remarked that the Ag 12 (μ 12 -Br) pattern is unprecedented, and μ 12 -X coordination is overall very uncommon in the literature. Apart from the above-discussed clusters, it was found only in [(μ 12 -Cl)@Ag 12 @Ag 48 (dppm) 12 ] 129 and [{TpMo(μ 3 -S) 4 Cu 3 } 4 (μ 12 -I)] − . 130…”
Section: Anion-templated Cu(i) and Ag(i) Clustersmentioning
confidence: 94%
“…It should be remarked that the Ag 12 (μ 12 -Br) pattern is unprecedented, and μ 12 -X coordination is overall very uncommon in the literature. Apart from the above-discussed clusters, it was found only in [(μ 12 -Cl)@Ag 12 @Ag 48 (dppm) 12 ] 129 and [{TpMo(μ 3 -S) 4 Cu 3 } 4 (μ 12 -I)] − . 130…”
Section: Anion-templated Cu(i) and Ag(i) Clustersmentioning
confidence: 94%
“…photoluminescence 35. A deeper understanding of the electronic structure is required for practical applications using their size-specific physicochemical properties.36−38 In this study, we synthesized three new anion-templated Ag NCs (1−3) containing a sulfide ion (S 2− )39 or a chloride ion (Cl − )40 as template anions by controlling the amount of thiol, reduction time, or the presence of countercations during synthesis. Single-crystal X-ray diffraction (SC-XRD) and electron spin resonance (ESR) spectroscopy revealed that clusters 1−3 have the chemical compositions [S@Ag 17 (S-4CBM) 15 (PPh 3 ) 5 ] 0 [1; S-4CBM = 4-chlorobenzene methanethiolate (Scheme S1a)], [S@Ag 18 (S-4CBM) 16 (PPh 3 ) 8 ] 0 (2), and [Cl@Ag 18 (S-4CBM) 16 (PPh 3 ) 8 ][PPh 4 ] (3) (Table1).…”
mentioning
confidence: 99%
“…Br–Cu: 2.977 Å (R = n Bu, R′ = C 2 Ph)), 14 [(μ 12 -Cl)@Ag 12 @Ag 48 (dppm) 12 ] (avg. Cl–Ag: 2.917 Å), 19 and [{TpMo(μ 3 -S) 4 Cu 3 } 4 (μ 12 -I)] − (avg. I–Cu: 3.195 Å).…”
Section: Resultsmentioning
confidence: 99%